2020
DOI: 10.1055/a-1223-2525
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinic Acid Intravitreal Implants: A New Therapeutic Approach for Ocular Neovascularization

Abstract: Rosmarinic acid, a plant-derived compound with antiangiogenic activity, can be applied for the treatment of ocular diseases related to neovascularization, such as diabetic retinopathy, macular edema, and age-related macular degeneration. These diseases represent the leading causes of blindness worldwide if they are not properly treated. Intravitreal devices allow for localized drug delivery to the posterior segment, increasing the drug bioavailability and promoting extended release, thus, reducing side effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Antiangiogenic activity of MEL was assessed by the chicken embryo CAM assay, as previously described by Vieira et al. (2020) .…”
Section: Methodsmentioning
confidence: 99%
“…Antiangiogenic activity of MEL was assessed by the chicken embryo CAM assay, as previously described by Vieira et al. (2020) .…”
Section: Methodsmentioning
confidence: 99%
“…In concurrence with these results, placebo‐controlled randomized clinical trials in human subjects diagnosed with aging‐associated memory impairments reported no significant side‐effects of an aqueous spearmint extract containing RA on multiple tolerability parameters indicative of toxicity; including vital signs, endocrine and hematological and biochemical assessment of blood, and subjective gastrointestinal assessment (Lasrado et al, 2017; Nieman et al, 2015). Lastly, studies have also confirmed inconsequential detrimental effects of different nanoformulations loaded with RA on multiple parameters indicative of gut microbiome dysbiosis, and liver and kidney dysfunction, and hematological, biochemical, genotoxic, cytotoxic and oxidative damage (Reis et al, 2016; Vieira et al, 2020).…”
Section: Pharmacokinetics and Tolerability Of Ramentioning
confidence: 91%
“…Numerous compounds, namely, artemisinin (a lactone isolated from Artemisia annua) [64], astragaloside (a cycloartane-type glycoside isolated from Astragalus membranaceus) [65], celastrol (a quinone methide triterpene) [70], carnosic acid (a phenolic diterpene isolated from rosemary extract) [69], diarylheptanoids isolated from Curcuma comosa [75], diphlorethohydroxycarmalol (a phlorotannin isolated from brown macroalga Ishige okamurae) [76], FLZ (a novel synthetic cyclic analogue of natural squamosamide isolated from Annona glabra) [77,78], glycyrrhizin (a glycoside isolated from licorice roots (Glycyrrhiza glabra)) [81], GPETAFLR (a biopeptide isolated from Lupinus angustifolius) [82], gypenosides (dammaranetype triterpene saponins isolated from Gynostemma pentaphyllum) [83], kinsenoside isolated from Anoectochilus roxburghii [84], phillyrin (a lignan isolated from dried fruit of Forsythia suspense) [85], rosmarinic acid isolated from Rosmarinus officinalis [86] and total saponins isolated from rhizomes of Paris polyphylla [87] also demonstrated promising protective effects against oxidative damage in preclinical models.…”
Section: Other Active Compoundsmentioning
confidence: 99%
“…A recent, remarkable trial on New Zealand white rabbits demonstrated the efficacy of therapeutically designed rosmarinic acid-poly lactic-co-glycolic acid (PLGA) implants in impeding ocular neovascularization. This strategy takes a long-term view toward the possible use of PLGA, a biodegradable polymer as an implantable intravitreal device to promote prolonged and controlled release of rosmarinic acid in vitreous humor [86].…”
Section: Other Active Compoundsmentioning
confidence: 99%